Some Phenomenological and Metaphisycal Aspects of Human Creativity - Dolidze, Mamuka (Investigaciones Fenomenológicas, 2014)
The author gets human creativity to bridge phenomenology and metaphysics. He examines closely the poetical principle of Edgar Allan Poe and considers the artwork (poem) as a phenomenon appealing to the metaphysical beauty. He also considers the problem of free-dom in phenomenological and metaphysical aspects of creativity. To harmonize the freedom and phenomenology the author offers to differentiate two kinds of intentionality: “intentionality to” and “intentionality from”. The first is reducible to the purposefulness of events and refers to the constitutive function of consciousness, the latter implies the human creativity and freedom as an act of differentiation of phenomenon from its previous limits. The incipient point of the second form of intentionality seems to be a metaphysical object, which is worth considering as an inexhaustible source of the world of phenomena. El autor considera la creatividad humana pare tender un puente entre fenomenología y metafísica. Examina de cerca el principio poético de Edgar Allan Poe y considera la obra de arte (el poema) como un fenómeno que apela a la belleza metafísica. Considera el problema de la libertad en relación a los aspectos fenomenológicos y metafísicos de la creatividad. Para armonizar la libertad y la fenomenología, el autor propone diferenciar dos tipos de intencionalidad: “intencionalidad a” y “intencionalidad de (desde)”. La primera es reducible a la intencionalidad (purposefulness) de los hechos y se refiere a la función constitutiva de la conciencia; la segunda implica la creatividad humana y la libertad como un acto de diferenciación del fenómeno de sus límites anteriores. El punto de partida de la segunda forma de intencionalidad parece ser un objeto metafísico, el cual merece la pena considerar como una inagotable fuente del mundo de los fenómenos.